Atividades com raciocínio lógico para a aprendizagem significativa em ciências - Brisola, Flávia Esteves (2019)
This study deals with a discussion around problem-based learning (PBL), through logical reasoning activities, methodology in which learning topics are presented through concepts related to teaching content, in the face of problems the student develops strategies to solve them, based on previous knowledge acquired throughout the teaching-learning process. The study has as its goal: Analyze how logical reasoning activities help students in the final years of elementary school to build meaningful science learning.This was an applied and exploratory study of qualitative data analysis that had as research field three classrooms from the 8th grade of a public elementary school from the Ponta Grossa city, in Paraná state. Data were collected through questionnaires for teachers and students about understanding the use of logical reasoning in science activities and the logical reasoning activities performed with students were also used. To support the study the following subjects were regarded: Science teaching in Brazil, Science teaching in the final years, subdividing into Teaching about the human body, Meaningful Learning in Science, Learning in Science based on problem solving with the development of logical reasoning and Meaningful learning based on the use of metacognitive and cognitive strategies. As a result, it was observed that the activities allow the development of strategies that if anchored in previous knowledge, allowed the student to obtain meaningful learning. The present study had as its final product the development of a pedagogical activity notebook, which can support the teachers’ work in the classroom, in the development of the students' logical reasoning, as an instrument to be used in the teaching and learning process. The activities contained in the notebook have as content systems, more specifically: Genitals; Urinary; Skeletal; Respiratory; Circulatory; Food/ Genetics and Chemical Elements, for being an integral part of Science Education.